Direct injection nebulizer with replaceable capillary for micro samples analysis by inductively coupled plasma-optical emission spectrometry (2017)
The analytical performance of a low cost direct injection high efficiency nebulizer (DIHEN) with replaceable capillary is evaluated and compared with a high efficiency nebulizer HEN-cyclonic spray chamber arrangement for sample introduction at lower solution uptake rates in inductively coupled plasma optical emission spectrometry (ICP-OES). The system allows the use of a replaceable capillary and optimization of the aerosol generation. The study was performed in terms of the main analytical figure of merits (i.e., sensitivity, limits of detection and signal stability) for plain water solutions and matrix effects caused by nitric acid and sodium in ICP-OES. In general, the DIHEN with replaceable capillary offers better sensitivities than the HEN-Cyclonic system and for some elements, improved detection limits (DL) in the range of 1.1–3.8 ng mL 1 for Ba,Mg, Zn 206.2–200 nm and Zn 213.8–856 nm were obtained. Strontium’s DL was comparable with both systems and those for Cd and Mn were slightly worse. Short-term precision for this unit is not as good as the HEN-Cyclonic system, but being less than 2%, it can still be considered acceptable. It was more susceptible to changes in matrix composition, being ca. 18% the acid depressive effect and 7% due to sodium with the DIHEN compared to the conventional nebulizer-spray chamber arrangement (13 and 3% acid and sodium depressive effect, respectively). The utility of the developed unit is explored analyzing three certified materials (bovine liver, rice and wheat flours) and the experimental results are within the certified values. The ability of the DIHEN with replaceable capillary to analyze real micro samples (samples reconstituted in 150 mL deionized water) was demonstrated by the determination of Ca, Cd, Cu, Mg, Mn, Sr, and Zn in individual scorpion venoms samples. One of the main advantages over other arrangements is that it can be easily constructed in the laboratory.